Taxonomia, distribuição e abundância da família Aristeidae (Penaeoidea: Dendrobranchiata) do talude da costa central do Brasil, coletada pelo Programa Revizee - Score Central - Tavares, Carolina (2005)
The family Aristeidae is predominantly deep-water distributed, being either benthic dwellers or members of the meso and bathypelagic fauna. They have a greal abundance in the water column, and play a major role in the food chain of the oceans. The family as now defined consists of nine genera, most of them greatly distributed in Atlantic and Indo-Pacific oceans. Of these genera, six have been recorded from eastern Atlantic. The family Aristeidae in Brazil is poorly known, with only three species recorded from off the Brazilian coast: Plesiopenaeus edwarsianus (Jonhson, 1867), Aristaeomorpha foliacea (Risso, 1827) and Hepomadus tener Smith, 1884 The Revizee Program made trawlings between Rio Real (llºS) and Cabo de São Tomé (22º), and a large scientific collection of deep-sea crustaceans was formed. The Revizee trawlings were made between 1999 may and 2000 june, between 200-2000 meters depth. The material was examined and eight species were found. Besides those three species previously recorded from off Brazilian coast, that have their latitudinal distribution enlarged, five species are new records to Brazil: Aristeus antillensis A. Milne Edwards & Bouvier, 1909, Hemipenaeus carpenteri Wood-Mason, 1891, Plesiopenaeus armatus (Bate, 1881), Plesiopenaeus coruscans (Wood-Mason, 1891) and Aristeus antennatus (Risso, 1816). Results showed that, some Aristeidae species are greatly abundant between 500 and 750 meters, others are more abundant between 750 and 1250meters, and deeper ones are more abundant between 1250 and 2000 meters. A positive correlation between discharge of rivers and high abundance of Aristeidae species was observed. An identification key for Aristeidae species of Brazil is given.